Image coding for transmission over wireless CDMA channels. - Huang, Xiaodong. (University of Ottawa (Canada), 2002)
This thesis provides a comparative analysis of sentencing patterns in two time periods separated by seventeen years. Research of this type has not been attempted previously, due to the limited availability of historical sentencing data. Using statistics obtained from the Royal Canadian Mounted Police's Fingerprint System from 1983--1984 and the Canadian Centre for Justice Statistics' Adult Criminal Court Survey for 1999--2000, this study examines whether recommendations made by various federal inquiries into sentencing have affected judicial decision-making at the trial court level. At the core of this discussion is an examination of those initiatives aimed at reducing the use of imprisonment as a sanction. Comparisons reveal that sentencing patterns in 1983--1984 differed significantly from those present in 1999--2000. In some cases, it appears as though the changes were in accordance with recommendations of the federal inquiries whereas in others, the patterns that were discovered seemed to indicate that judges ignored or even defied the directives given. With regard to the promotion of community sanctions, there was an overwhelming increase in the use of probation. In contrast, the findings with respect to the use of imprisonment were more ambiguous; while the overall decrease in the rate of incarceration had been a stated objective, the manner in which this reduction was achieved appears to contradict the recommendations of the inquiries. Essentially, this study shows that, despite the wealth of time and research devoted to the reform of the sentencing process in this country, the impact of these efforts on judicial practices has been minimal.
Keywords: Engineering, Electronics and Electrical.